Dysbiosis of the gut microbiota and colorectal cancer: the key target of molecular pathological epidemiology - Kosumi, Keisuke; Mima, Kosuke; Baba, Hideo; Ogino, Shuji (Journal of Laboratory and Precision Medicine, 2018)
Microbiome is a dramatically advancing research field in the study of human cancers (1). Microbial distribution varies spatially and temporally from the mouth to the rectum during the individual’s lifetime. These gut bacteria maintain intestinal homeostasis by regulating various biological functions such as mucosal barrier, immunity, and metabolic processes.